Migration and citizenship among the Afghan community in Iran - Rohani, Sarah Pour (2014)
This thesis presents the results of Iranian women’s marriages with Afghan illegal immigrants. The initial idea was to determine the citizenship status of these families’ in Iran. This research looks at the status of Afghans in Iran who married Iranian women. Because of the intolerable conditions in Afghanistan, they have flown to other countries especially Iran. They hoped that the marriage with Iranian women may help them to obtain Iranian citizenship. The Iran government not only accepted to grant Iranian citizenship to them, but their children could not get any Afghan or Iranian identity. My hypothesis in this research is that the Iranian government will not grant Iranian citizenship to these families due to various reasons such as protecting the national security. The statics documents results supported my hypothesis by showing the growing population is one of various factors that can be a threat to national security. For his reason, the Iranian government cannot grant Iranian citizenship to these Afghans. Granting Iranian citizenship to Afghans will open Iran’s borders to other immigrants to come to Iran. The consequence of this action caused an already large population in Iran to grow even with more negative consequences, Providing benefits and facilities like education, health and housing and the most important economic problem for original Iranian are the Iranian government’s concern. And a very large population will create more difficulties for Iran and pose threats the growing population implies unemployment and more economic problems which, if not addressed in time, can threaten Iran’s national security.